The association of body mass index and weight waist adjustment index with serum ferritin in a national study of US adults - Hao Han; Ping Ni; Siqi Zhang; Xiaojuan Ji; Mingli Zhu; Wanyu Ma; Hongfeng Ge; Hailiang Chu (European Journal of Medical Research, 2023)
Abstract Background Abnormal serum ferritin levels are associated with a variety of diseases. Meanwhile, abnormal serum ferritin is influenced by a variety of risk factors, but its correlation with obesity remains poorly described. Objective This study aimed to investigate the association of body mass index (BMI) and weight waist adjustment index (WWI) with serum ferritin in US adults. Methods Participants in this study took part in the National Health and Nutrition Examination Survey (NHANES) prior to the pandemic from 2017 to March 2020. Serum ferritin was used as the sole response variable and BMI and WWI were used as independent variables. Multiple linear regression was used to assess the relationship between serum ferritin and the independent variables, and smoothed curve fitting and threshold effects analysis were performed to assess the presence of non-linear relationships. To validate the sensitive individuals for the correlation between the independent and the dependent variables, a subgroup analysis was performed. Results A final total of 7552 participants were included in this study. Both independent variables had a positive relationship with serum ferritin, with effect values of (β = 0.68, 95% CI: 0.17–1.19) when BMI was the independent variable and (β = 8.62, 95% CI: 3.53–13.72) when WWI was the independent variable in the fully adjusted model. This positive association between the two obesity-related indexes and serum ferritin became more significant as BMI and WWI increased (P for trend < 0.001). In subgroup analyses, the positive association between the independent variables and serum ferritin was more pronounced in participants who were male, 40–59 years old, white, and had diabetes and hypertension. In addition, smoothed curve fitting and threshold effects analysis demonstrated a linear positive association of BMI and WWI with serum ferritin. Conclusions In the US adult population, while there was a linear positive association of WWI and BMI with serum ferritin, the effect values between WWI and serum ferritin were more significant. Male, 40–59 years old, white, participants with diabetes and hypertension should be cautious that higher WWI might entail a risk of higher serum ferritin levels.